Caracterização espectroscópica de peixe do período cretáceo (Bacia do Araripe) - Lima, Ricardo Jorge Cruz; Saraiva, Antonio Alamo Feitosa; Lanfredi, Silvania [UNESP]; Nobre, Marcos Augusto de Lima [UNESP]; Freire, Paulo de Tarso Cavalcante; Sasaki, José Marcos (Sociedade Brasileira de Química, 2007)
The study of fossils has made considerable progress over the last years as a result of the use of new experimental techniques. This paper describes the chemical composition of a fossilized fish of the Cretaceous period, from a 100 million-year-old, material originated from the Araripe Basin (northeastern Brazil). The chemical composition of the fossilized fish was analyzed by means of X-ray powder diffraction and Fourier transform infrared spectroscopy (FT-IR). The spectroscopic study has proven that the main substances found in the fossilized fish are CaCO3 and Ca5(PO4)3(OH). A tentative mechanism to explain the fossilization process is also given.
Spectroscopic characterization of a fish of the cretaceous period (Araripe Basin)
Keywords: Fossil; X-ray diffraction; Fourier transform infrared spectroscopy